PENGARUH SIKAP DAN PENDIDIKAN KEWIRAUSAHAAN PADA MINAT BERWIRAUSAHA - Hendra Prasetya; Ricky Angga Ariska (EKOBIS, 2021)
The problem in this study is whether entrepreneurial attitudes and education partially have a significant on entrepreneurial interest student of management study program, Faculty of Economics and Business, Wijaya Kusuma University, Surabaya. The aim is to determine the effect entrepreneurial attitudes and education on interest in entrepreneurship whether significant or not. Variable identification consists of independent ang dependent variables. The independent variables are entrepreneurial attitudes and education, while the dependent variable is interest in entrepreneurship. The sample is determined by purposive sampling while the analysis is using multiple linear regression. The results of hypothesis testing carried out by t test are attitudes have a positive and significant effect on entrepreneurial interest in students of management study program of Faculty of Economics and Business University of Wijaya Kusuma Surabaya while entrepreneurship education has a positive effect but does not have a significant on entrepreneurship in interest. To increase the interest in entrepreneurship among students, the cultivation of entrepreneurial attitudes needs to be fostered, among others, through the culvitation of self-confidence, inisiative, a spirit of leadership, courage in taking risks and being creative. The Faculty of Economics and Business, University of Wijaya Kusuma Surabaya and lecturers of the Entrepreneurship Course must do their best to make this course a trigger for the emergence entrepreneurial interes among students. Things that can be done include rearranging course materials, the learning process, lecture facilities and infrastructure as well as entrepreneurial practice activities. Keyword: attitude, entrepreneurship education, entrepreneurial interest.